PENGARUH PREFERENTIAL TRADE AGREEMENT TERHADAP IMPOR KAPAS DARI PAKISTAN BAGI INDUSTRI TEKSTIL DI INDONESIA 2013-2015 - Wulandari, Puput Ayu; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research analyzed the Effect of Preferential Trade Agreement For Cotton Import From Pakistan to Indonesian Textile Industry. Indonesia as the country textile production 6th in the world, has a deficiency in the supplying of the main raw material for the manufacture of textiles, specifically cotton fiber. Indonesia still depends on cotton import commodities from several countries, one of them is from Pakistan. The price increase of cotton import commodities which has increased every year makes Indonesia and Pakistan taken an agreement called IP-PTA (Indonesia-Pakistan Preferential Trade Agreement) on September 1th, 2013 concerning the reduction of import duties on cotton imports for Indonesia.This research uses Qualitative Research, with the research library method. Some of the data obtained comes from books, journals, articles, newspapers, internet and other media. In this study also used the Perspective of Neoliberalism, the theory of Economic Integration proposed by Bella Balassa and use level of nation-state analysis in looking at the cases studied. In this research, Indonesia-Pakistan as the international actors.The IP-PTA agreement is very helpful for Indonesia in meeting domestic demand for cotton fiber at low prices. The textile industry is very influential for Indonesia, because the textile industry was able to increase the country's foreign exchange which was previously USD 12.46 to USD 12.59 billion (10.1%). Under the agreement Indonesia benefited from a reduction in the cotton import tariff from 15% to 9%. Pakistan benefits from the reduction of the import duty from PTA palm oil from 15% to 0%.Keyword : (IP-PTA Indonesia-Pakistan Preferential Trade Agreement), PTA (Preferential Trade Agreement, Reduction of Import duties